Medical Ethics And Legal Duties Of A Doctor In Ancient Time - Anita; Upadhyay, Parmanand; Godara, Sunita; Rajpurohit, Gourishankar (International Research Journal of Ayurveda & Yoga, 2021)
Agadtantra is one among the Ashtangas of Ayurveda. Agadtantra evam vyavahara ayurveda is a branch which deals with the toxicology, forensic medicine, medical jurisprudence. Vyayhara ayurveda made by two words Vyavahar and Ayurveda. Vyavahar means conduct behaviour which included in medical ethics. In medical ethics, the duty of medical practitioner related with law and prohibition rules are described. The ethical code in medicine have found their place in very beginning as Ayurveda is the most ancient medical science. The references of medical ethics including the duty of physician, ideal qualities of physician, surgeon qualities, medicinal dose (according to nature of people) and medicinal dosage for child, details of post- mortem and anaesthesia were described in the various samhitas of Ayurveda. In this article we will Elobarate and explore the knowledge of medical ethics in that time.